If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -7x = -15 + -3x Solving 5 + -7x = -15 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 5 + -7x + 3x = -15 + -3x + 3x Combine like terms: -7x + 3x = -4x 5 + -4x = -15 + -3x + 3x Combine like terms: -3x + 3x = 0 5 + -4x = -15 + 0 5 + -4x = -15 Add '-5' to each side of the equation. 5 + -5 + -4x = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = -15 + -5 -4x = -15 + -5 Combine like terms: -15 + -5 = -20 -4x = -20 Divide each side by '-4'. x = 5 Simplifying x = 5
| -0.25y=16 | | x-2y+5=8 | | 8x^3+10x^2-5x-3=0 | | X+(-6)=9 | | -10p+9=12 | | 14c+35= | | 68-4*(3-1)3=c | | 6b+8= | | x^2+4bx+2b=0 | | X^3+2x^2-8x= | | 2x^12+3x= | | -3=5-t | | 173x+12=185 | | 173x+12=194 | | 173x+12=195 | | 3p-6= | | 173x+12=4278 | | 4b^2+7b+10=0 | | 4x^2-24x+100=0 | | 3q-40-4a=7a | | 3x+28=78 | | 3b-3=6(b+5) | | 4+b=-1 | | g+(-18)=-36 | | 3(8-3)6-1=p | | 16+t=-9 | | 13-4*n=11+2*n | | (3*5-5)(5-1)=x | | 4p-5=18 | | -7b-5(b-4)= | | x^2-7x-7=0 | | x^2+10x+39=-3x+3 |